Relationship of cognitive decline with glucocerebrosidase activity and amyloid‐beta 42 in DLB and PD - Gonzalez, Maria Camila; Oftedal, Linn; Lange, Johannes; Tovar‐Rios, Diego Alejandro; Tysnes, Ole‐Bjørn; Paquet, Claire; Marquié, Marta; Boada, Mercè; Alcolea, Daniel; Rejdak, Konrad; Papuc, Ewa; Hort, Jakub; et al. (Annals of clinical and translational neurology, 2025)
Objective Dementia with Lewy bodies (DLB) and Parkinson's disease (PD) share clinical, pathological, and genetic risk factors, including GBA1 and APOEε4 mutations. Biomarkers associated with the pathways of these mutations, such as glucocerebrosidase enzyme (GCase) activity and amyloid‐beta 42 (Aβ42) levels, may hold potential as predictive indicators, providing valuable insights into the likelihood of cognitive decline within these diagnoses. Our objective was to determine their association with cognitive decline in DLB and PD. Methods A total of 121 DLB patients from the European‐DLB Consortium and 117 PD patients from the Norwegian ParkWest Study were included in this study. The four most commonly associated variants of GBA1 mutations (E326K, T369M, N370S, L444P), APOEε4 status, and cerebrospinal fluid (CSF) Aβ42 levels and GCase activity were assessed, as well as global cognition using the Mini‐Mental State Examination. Linear mixed‐effects regression models were used to evaluate the association of CSF biomarkers with cognitive decline in each diagnostic group, adjusted for age, sex, education, and genetic mutation profile. Results Low CSF Aβ42 levels were associated with accelerated cognitive decline in DLB, whereas reduced CSF GCase activity predicted faster cognitive decline in PD. These associations were independent of GBA1 gene mutations or APOEε4 status. Interpretation Our study provides important evidence on the relationship between brain Aβ deposition and GCase activity in the Lewy body disease spectrum independent of their genetic mutation profile. This information could be relevant for designing future clinical trials targeting these pathways.